Formation of environmentally persistent free radicals (EPFRs) on ZnO at room temperature: Implications for the fundamental model of EPFR generation - Patterson, Matthew C. (Chem Phys Lett, 2016)
Environmentally persistent free radicals (EPFRs) have significant environmental and public health impacts. In this study, we demonstrate that EPFRs formed on ZnO nanoparticles provide two significant surprises. First, EPR spectroscopy shows that phenoxy radicals form readily on ZnO nanoparticles at room temperature, yielding EPR signals similar to those previously measured after 250°C exposures. Vibrational spectroscopy supports the conclusion that phenoxy-derived species chemisorb to ZnO nanoparticles under both exposure temperatures. Second, DFT calculations indicate that electrons are transferred from ZnO to the adsorbed organic (oxidizing the Zn), the opposite direction proposed by previous descriptions of EPFR formation on metal oxides.